Применение невзрывчатых разрушающих составов при проведении выработок вслед за лавой - Касьян, Н.Н.; Сахно, И.Г. (Геотехническая механика, 2012)
Запропоновано спосіб проведення гірничих виробок слідом за лавою, що грунтується на руйнуванні порід за допомогою невибухових руйнуючих складів (НРС). Отримані формули для розрахунку параметрів бурових робіт при реалізації способу. Наведена конструкція патрона НРС, що дозвляє вирішити технологічні питання доставки, фіксації НРС в шпурі, та управляння напрямом руйнування порід. The method of leadthrough the mountain making is offered right behind longwall which is based on destruction of breeds by non-explosive destroying compositions. The got formulas are for the calculation parameters of borings works during realization of method. Resulted construction the cartridge of non-explosive destruction compositions, that lets to decide the technological questions of delivery, fixing of compositions in hole, and management by direction of destruction breeds.